Diamond–coated ultrasonic tip decreases debris and uninstrumented surface after preparation of curved canals with isthmus - Maria Luiza GIOSTER–RAMOS; Mariana Mena Barreto PIVOTO–JOÃO; Jáder Camilo PINTO; Juliane Maria GUERREIRO–TANOMARU; Mário TANOMARU–FILHO (Brazilian Oral Research, 2023)
Abstract The aim of this study was to evaluate root canal preparation with nickel titanium rotary instruments and complementary preparation with ultrasonic tip in curved canals of mandibular molars with isthmus. Twenty–eight mesial roots of mandibular molars with curvature between 20° and 40° and presence of isthmus throughout the entire extension of the root canals were prepared using ProDesign Logic CM (PDL) up to size 40.05, or HyFlex EDM (HFEDM) up to size 40.04. Complementary preparation was performed in the isthmus region using the ultrasonic insert E18D (Helse, Istmo Diamantada). The root canals were scanned using micro–CT (SkyScan 1176) at 9 µm voxel size before and after each preparation step. Transportation, percentage of increase in volume, debris and uninstrumented surface (UNS) were evaluated. Mann Whitney, Wilcoxon, paired and non–paired t–tests were used for statistical analysis (α = 0.05). The canals prepared with PDL and HFEDM obtained similar results for all the variables assessed before using E18D (p > 0.05). E18D significantly decreased the percentage of debris and UNS values in both Groups (p < 0.05). The complementary preparations with E18D caused a smaller quantity of debris in the isthmus of the canals previously prepared with PDL in comparison with HFEDM (p < 0.05). PDL and HFEDM provided similar root canal preparation. PDL promoted a smaller quantity of Debris in the isthmus than HFEDM after using E18D. E18D significantly improved cleaning, and reduced Debris and UNS.